Uncovering Digital and AI Competency Gaps: A Qualitative Study of Generation X Employees in the UK Private Higher Education Sector - Khawaja, Sarwar (Digital Repository of Theses, 2025)
This qualitative doctoral study investigated the digital and Artificial Intelligence (AI) competencies of Generation X professionals within the UK private higher education sector. Employing a thematic analysis of 15 in-depth, semi-structured interviews, the research explored their lived experiences, self-perceptions, motivations, and attitudes towards digital transformation. Four principal themes emerged: "The Gen X Adaptive Journey: From Necessity to Fluency," highlighting their pragmatic digital proficiency; "Navigating Institutional and Systemic Barriers," detailing challenges like time constraints, institutional inertia, and inadequate support; "The Double-Edged Sword of AI," revealing a dual perception of AI's opportunities for efficiency and profound ethical threats; and "The Evolving Professional Identity and Institutional Voice," reflecting shifts in confidence and concerns about their influence in digital strategies. The findings underscore Generation X's crucial role as adaptable "digital immigrants" and emphasise the imperative for private higher education institutions to develop human-centred, ethically informed digital strategies. This study contributes to generational theory in technology adoption and offers practical recommendations for tailored professional development and inclusive digital governance, ensuring this experienced cohort's vital contribution to the evolving educational landscape. Keywords: Generation X, Digital Competencies, AI Competency, Digital Transformation, Workplace Learning, Private Higher Education UK